Three distal root canals in mandibular first molar with different canal configurations: Report of two cases and literature review - Parul Bansal; Vineeta Nikhil; Shashank Shekhar (Wolters Kluwer Medknow Publications, 2015)
With the increasing number of reports of aberrant root canal morphology, the clinician needs to be aware of the variable anatomy. Various case reports have been published with the finding of middle mesial canal in mandibular first molar, however finding of three distal canals in distal roots of mandibular first molar is rare. This article reports endodontic management of two mandibular first molars presented with three distal canals present in a single distal root (Sert and Bayirli type XVIII) and distal and distolingual root.